The role of the north labuhanbatu regency government in the development of the UMKM UD Batik Jelujur Labura - Dimas Ardika; Muhammad Syukri Albani Nasution; Aqwa Naser Daulay (Indonesia Auditing Research Journal, 2026)
Local culture-based Micro, Small, and Medium Enterprises (MSMEs) play an important role in supporting regional economic development while preserving the cultural identity of the community. One of the culture-based MSMEs that is developing in North Labuhanbatu Regency is the Labura Jelujur Batik MSME. However, the development of this MSME still faces various obstacles, both in production, marketing, and institutional support. This study aims to analyze the role of the North Labuhanbatu Regency Government in the development of the Labura Jelujur Batik MSME and identify the challenges faced by business actors. The study used a descriptive qualitative approach with in-depth interviews and observations of MSME actors and related local government officials. The results show that the North Labuhanbatu Regency Government has carried out its role around 70% in the development of the Labura Jelujur Batik MSME. The government's role is more dominant as a facilitator and mediator, while the regulatory function is not optimal due to the absence of specific regulations related to the Labura Jelujur Batik MSME. Government support includes providing a complete set of batik tools, batik training in Kalimantan in 2024, marketing assistance through annual cultural exhibitions, and product innovation training with batik artisans from outside the region, such as Kisaran and Rantau Prapat.